2016
DOI: 10.1186/s12872-016-0412-2
|View full text |Cite
|
Sign up to set email alerts
|

A unique association of arrhythmogenic right ventricular dysplasia and acute myocarditis, as assessed by cardiac MRI: a case report

Abstract: BackgroundArrhythmogenic right ventricular dysplasia (ARVD), is a genetic disorder of the heart, which mainly involves the right ventricle. It is characterized by hypokinetic areas at the free wall of the right ventricle (RV) or both ventricles, where myocardium is replaced by fibrous or fatty tissue. ARVD is an important cause of ventricular arrhythmias in children and young adults. Although the transmission of the disease is based on hereditary, in young adults it may not show any symptoms. The main differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…A recent published study demonstrated that de novo variants in ARVC are rare . Increasing evidence supports the hypothesis that myocardial injury from myocarditis contributes to the onset of ARVC, and hence, myocarditis may be part of the clinical presentation of ARVC. An inflammatory process secondary to infection or immune mechanism has been postulated to be the trigger for myocardial injury in ARVC, in so called hot phases of the disease.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A recent published study demonstrated that de novo variants in ARVC are rare . Increasing evidence supports the hypothesis that myocardial injury from myocarditis contributes to the onset of ARVC, and hence, myocarditis may be part of the clinical presentation of ARVC. An inflammatory process secondary to infection or immune mechanism has been postulated to be the trigger for myocardial injury in ARVC, in so called hot phases of the disease.…”
Section: Discussionmentioning
confidence: 85%
“…Despite abnormalities in the right ventricle (RV) being the predominant finding, it has been reported that patients with ARVC may also have left ventricle (LV) involvement, and indeed, severe LV impairment can sometimes be the initial manifestation of the disorder . Inflammatory cell infiltrates have been described in patients with ARVC, and some patients with ARVC present with signs and symptoms accompanied by electrocardiogram (ECG) changes as well as echocardiography (ECHO) and cardiac magnetic resonance (CMR) findings consistent with myocarditis …”
Section: Introductionmentioning
confidence: 99%
“…The presence of mature fat or “fibro-fatty replacement of myocardium” in endomyocardial biopsies is a hallmark of arrhythmogenic right ventricular cardiomyopathy [ 33 - 35 ]. However, the presence of mature epicardial fat in the endomyocardial biopsy is common.…”
Section: Discussionmentioning
confidence: 99%
“…This is an acute phase, characterized by chest pain, ECG changes of the ventricular repolarization, and an increase in myocardial enzymes. Despite the fact that ARVC is predominantly a genetic disease, a frequent link with an inflammatory process has been demonstrated and myocardial inflammatory infiltrates are frequently detected in patients with ARVC [19]. An etiological role of myocarditis has been supposed, especially in the initial phase of ARVC.…”
Section: From Myocardial Cell Mechanisms To the Ecg Patternmentioning
confidence: 99%